Structural and electronic properties of zinc blende B xAl 1-xN yP 1-y quaternary alloys via rst-principle calculations - Abdiche, A.; R., Baghdad; R., Khenata; R., Riane; Yarub K.A., Al - Douri; M., Guemou; S., Bin-Omran (Elsevier B.V., 2012)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home